A Systematic Review of Endocrine Therapy for Improved Reproductive and Metabolic Outcomes in PCOS Women - Nur Aini Lutfi Rahmawati; Esti Yunitasari; Ni Ketut Alit Armini; Padoli Padoli; Suharyono Suharyono (Pediomaternal Nursing Journal, 2021)
Introduction: Polycystic ovarian syndrome (PCOS) is characterized by infrequent or absent ovulation as well as elevated levels of androgens and insulin (hyperinsulinaemia). The purpose of this study was to determine the efficacy of endocrine treatment in improving reproductive and metabolic outcomes in women with PCOS.Methods: We searched the following databases from inception to Maret 2020: PubMed, Proquest, ScienceDirect, Scopus and CINAHL. We investigated at metformin, clomiphene citrate, metformin plus clomiphene citrate, D-chiro-inositol, statins, and resveratrol as treatments. We compared them to each other, as well as to a placebo or no therapy. The quality of the evidence ranged from extremely low to moderate. The risks of bias (poor reporting of technique and inadequate outcome data), imprecision, and inconsistency were the limitations.Results: Although the evidence quality was low, our latest evaluation indicated that metformin alone may be superior to placebo for live birth. Data for live birth were equivocal when metformin was compared to clomiphene citrate, and our conclusions were hampered by a paucity of evidence. Body mass index (BMI) varies in the results, emphasizing the need of stratifying data by BMI.Conclusion: Clinical pregnancy and ovulation improvements demonstrate that clomiphene citrate is still preferred to metformin for ovulation induction in obese women with PCOS.